Epidemiologic and clinical features of cyanobacteria harmful algal bloom exposures reported to the National Poison Data System, United States, 2010-2022: a descriptive analysis - Rebecca A. Bloch; Michael C. Beuhler; Elizabeth D. Hilborn; Grace Faulkner; Sarah Rhea (BMC, 2024)
Abstract Background Harmful algal bloom occurrences have been increasingly reported globally and over time. Exposure to the variety of toxins and co-contaminants that may be present in harmful algal blooms can cause illness and even death. Poison control data is a valuable public health information source that has been used to characterize many types of toxin exposures, including harmful algal blooms. Prior studies have been limited by location and time, and knowledge gaps remain regarding cyanobacteria harmful algal bloom (cyanoHAB) exposure circumstances, and the breadth and severity of associated clinical effect. Methods The objective of this study was to characterize epidemiologic and clinical features of cyanoHAB exposure cases reported to 55 US poison control centers and available in the National Poison Data System (NPDS). We identified 4260 NPDS cyanoHAB exposure cases reported from 2010 to 2022, including symptomatic exposure cases with and without clinical effects related to the exposure and asymptomatic exposure cases. We assessed demographics; exposure routes, locations, chronicity; clinical effects; and medical outcomes. We calculated case rates annually and 13-year case rates by US geographic division. Results Over half of cyanoHAB exposure cases were children < 20 years old (n = 2175). Most cyanoHABs exposures occurred in a "public area" (n = 2902, 68.1%); most were acute (≤ 8 h) (n = 3824, 89.8%). Dermal and ingestion routes and gastrointestinal effects predominated. 2% (n = 102) of cases experienced a moderate or major medical outcome; no deaths were reported. National rates increased from 0.4 cases/1 million (1 M) person-years in 2010 to 1.4 cases/1 M person-years in 2022. The Mountain division had the highest 13-year rate (7.8 cases/1 M person-years). Conclusions CyanoHAB exposure case rates increased 2010-2022, despite a decrease in all-cause exposure cases during the same period. NPDS data provide valuable public health information for characterization of cyanoHAB exposures, an emerging public health challenge.